(untitled) (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
Substances synthesized on the basis of chloroacetylation reactions of phenol and its derivatives have high biological activity and are widely used in pharmaceuticals as antibacterial, analgesic and bactericidal drugs against pathogenic microorganisms [1]. Among these are substances such as adrenaline, noradrenaline, isadrin with high biological activity, which are used in medicine as immunostimulants, anti-diabetic and anti-cancer drugs, as well as in pharmaceuticals as hormonal drugs [2,3,4].